(3ZfjI GddHjH YfO ZjHI GdWHjHs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3HYO GdMeO ddg hHYO agPg QSGdI dWjaI GdMLe YRjRI GdYde JTJed Ydi eGdGHO efg ef Yde GdWH s
(3BNQgG (B:s
(3ef fXQ Edi hQO GdNWejI hgj Ydi TQLJg hOGQ Mhdg SHY OhQGJ , hdjcf gPG BNQ eG jhQO ai gPg GdQSGdI s
(3HQSe GdSdWGf CHj GdfUQ bGjJHGis
(3YdjgG JhbjY YHO GdHGSW Hf Ndjd GdeDQN GdeUQis
(3fSNI KGfjI NRGFfjI s
(3ePgHI GdWGdY s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdWHs